Exploring the Effects of North–South and South–South Research Collaboration in Emerging Economies, the Colombian Case. - Ordóñez‐Matamoros, Gonzalo; Vernot‐López, Michelle; Moreno‐Mattar, Ornella; Orozco, Luis Antonio (Review of Policy Research, 2020)
International research collaboration (IRC) is associated with both positive and negative effects on the performance of research in emerging economies. While some authors claim that North–South collaborations improve scientific quality and visibility for Southern countries, others claim that it may entail the reorientation of research to comply with Northern agendas. South–South collaborations are thought to increase the focus on local affairs, therefore leading to a relatively small number of scientific international publications appearing in "high quality" journals. Research on the impact of IRC beyond publications in international journals has been neglected despite the importance of other products in knowledge creation. This research uses a broad range of scientific outputs to empirically assess such assumptions and explore the outcomes of IRC in Colombia. Results from multivariate regressions and nonparametric analyses show that, contrary to common assumptions, Colombian research teams collaborating with partners from the global South report higher scientific production, while those collaborating with Northern countries seem to contribute to local knowledge the most.